How Words can be Misleading: A Study of Syllable Timing and “Stress” in Malay - Mohd Don, Zuraidah; Yong, J.; Knowles, Gerry (Time Taylor, 2008)

(untitled)
Duration and F0 were studied in a set of 111 Malay words produced by two female native speakers of Malay in order to identify the citation pattern. This preliminary study seemed to provide strong evidence for penultimate stress. Seen in a wider context, the evidence collapsed, and it became clear that Malay does not have word stress at all. The search for syllable timing led to doubts whether the syllable is a relevant unit in Malay prosody. The conclusion is that in view of the lack of complicating factors, Malay is an appropriate language to adopt for the study of prosodic structure, and for the development of automatic techniques for the analysis of spoken corpora.